Generation of stochastic cellular structures with anisotropic cell characteristics on the basis of ellipsoid packings. (March 2022) - Beckmann, Carla; Hohe, Jörg
Highlights: Algorithm for generation of anisotropic cellular structures. Extended method of the classical Voronoï process in Laguerre geometry. Cellular structures with pre-defined cell shape, size and orientation in space. Abstract: In the present study, an algorithm to generate anisotropic polygonal cellular structures based on ellipsoid packing is presented. The aim of this process is to obtain structures with different-sized cells which have significantly non-spherical aspect ratios and different orientations in space. The developed method is an extension of the classical Voronoï process in Laguerre geometry which is well-suited to define cell structures with an optimum surface to volume ratio. Different examples show that with this new space division process a number of cellular structures with extremely different characteristics of their cell shape, size and orientation in space can be computed. The generation of such different cellular structures is a useful tool in the multiscale analysis of anisotropic microstructured media with uncertain microstructures exhibiting microstructural anisotropies such as process-related anisotropic structural foams or anisotropic metallic grain agglomerates.